The Role of Tax Socialization, Education, and Government Support in MSME Compliance in Teras Malioboro - Prastyatini, Sri Lestari Yuli; Bissolihin, Al Hikni (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of tax socialization, education level, and government support on tax compliance among MSMEs in Teras Malioboro, Yogyakarta. The research employs a quantitative approach, using primary data collected through a questionnaire. The population consists of 888 MSME taxpayers at Teras Malioboro, with a sample of 90 respondents selected using simple random sampling. The data were analyzed using multiple linear regression to determine the effect of the independent variables on tax compliance. The results show that tax socialization and education level have a positive and significant impact on tax compliance, while government support does not significantly influence compliance. These findings suggest that enhancing understanding through effective socialization and education can improve MSME compliance. However, the study's scope is limited to a specific area, and further research is recommended to expand the sample and explore additional factors affecting tax compliance. Additionally, improved government support in tax services is suggested to enhance taxpayer compliance.